Dancers’ Somatic of Musicality - Marinberg, Niv; Aviv, Vered (Frontiers in Psychology, 2019)
Dancers often perform while synchronizing their movements to music as required by the choreographer. In this article we introduce the concept of categorizing choreography (or segments of it) according to its relationship to either the rhythm or the melody of the accompanied music, or to both. We demonstrate this distinction using several examples for each of these categories. In a pilot study, we composed choreographic sequences that were either melodic-based or rhythmic-based and taught them to professional dancers. The results showed that some dancers tend to synchronize their movements better to the rhythm and others to the melody. We refer to this tendency as the “dancers' somatic of musicality”. The findings highlight important differences in the somatic of musicality among dancers and call for attention of both choreographs and dancers to these differences since they bear on the way dancers learn, memorize and perform.